Differential Cost Analysis of Self-Production Decisions or Establishing Partnerships for Student as Entrepreneurs in the Digital Era - Maulida, Oktavianti; Winarko, Sigit Puji; Faisol, Faisol (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Objective: This research was conducted to analyze the application of differential costs in allocating production costs to self-produced decisions or establishing partnerships  in student businesses. Research Method: The research method used is descriptive research with a quantitative approach. Research Finding:  The results of the study show that the decision to establish partnerships incurs less production costs and saves more costs from being incurred compared to self-producing. Furthermore, students as entrepreneurs benefit greatly from the option of purchasing from outside sources by forming partnerships. Therefore, the allocation of production costs through external purchases through the establishment of partnerships is the most appropriate alternative for student businesses.